Provision of physical activity advice for patients with chronic diseases in Shenzhen, China - Rui Hu; Stanley Sai-chuen Hui; Eric Kam-pui Lee; Mark Stoutenberg; Samuel Yeung-shan Wong; Yi-jian Yang (BMC, 2021)
Abstract Background Physical activity (PA) may best be promoted to patients during clinical consultations. Few studies investigated the practice of PA advice given by physicians, especially in China. This study aimed to investigate the prevalence and contents of PA advice given by physicians in China and its association with patients' characteristics. Methods Face-to-face questionnaire asking the prevalence and contents of PA advice given by physicians was administered to adult patients in three major hospitals in Shenzhen, China. Attitude of compliance, stature, PA level, and socio-demographic information were also collected. Data was analyzed via descriptive statistics and binary logistic regression. Results Of the 454 eligible patients (Age: 47.0 ± 14.4 years), only 19.2% (n = 87) reported receiving PA advice, whereas 21.8%, 23.0%, 32.2%, and 55.2% of patients received advices on PA frequency, duration, intensity, and type, respectively. Male patients were more likely to receive PA advice from physicians [odds ratio (OR): 1.81; 95% confidence interval (CI): 1.08-3.05], whereas patients who were unemployed (OR: 0.16; 95% CI: 0.04-0.67), and who already achieved adequate amount of PA (OR: 0.29; 95% CI: 0.12-0.71) were less likely to receive PA advice. Conclusions Prevalence of physicians providing physical activity advice to patients is low, there is a pressing need to take intervention measures to educate healthcare providers.